The Effect of Therapeutic Communication on the Level of Self-Esteem in the Elderly: A Case Study of the Laut Dendang Village in the Percut Sei Tuan District - Pasaribu, Masdalifah; Lubis, Zulfahri; Siregar, Muhammad Kevin Humala Sakti; Fitria, Aida; Ma'ruf, Amar (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Therapeutic communication helps patients solve problems, reduce emotional and mental burdens, and take effective action, while self-esteem is an individual's evaluation of their ability, meaningfulness, success, and worth. This study examines how therapeutic communication affects elderly self-esteem in Laut Dendang Village in Percut Sei Tuan District. This study uses pre-test-post-test quasi-experimental design. This study has 62 participants. Purposive sampling yielded 17 respondents. The Paired T-test demonstrated that therapeutic dialogue affects senior self-esteem in Laut Dendang Village in Percut Sei Tuan District. The data analysis shows a mean value of and a p-value of 0.000. (2.100). Therapeutic dialogue raised self-esteem 2.1%. Therapeutic dialogue improves self-esteem in elderly Laut Dendang Village residents in Percut Sei Tuan District. This message substantially impacts weak and powerless self-confidence.